2019
DOI: 10.1093/femsec/fiz179
|View full text |Cite
|
Sign up to set email alerts
|

Age, gut location and diet impact the gut microbiome of a tropical herbivorous surgeonfish

Abstract: Herbivorous fishes play important ecological roles in coral reefs by consuming algae that can otherwise outcompete corals, but we know little about the gut microbiota that facilitates this process. This study focussed on the gut microbiota of an ecologically important coral reef fish, the convict surgeonfish Acanthurus triostegus. We sought to understand how the microbiome of this species varies along its gastrointestinal tract and how it varies between juvenile and adult fish. Further, we examined if the bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…sydneyanus (Clements et al, 2007 ; Moran et al, 2005 ). We again sampled free‐living animals collected from their natural environment and analysed gut contents from specific regions of the alimentary tract since microbial communities are known to vary along the gut of vertebrates (Donaldson et al, 2016 ), including fish (Jones et al, 2018 ; Parata et al, 2020 ). Sample variation due to season, temperature, location and food source was minimized by collecting all fish on the same day from the same site at Great Barrier Island, Hauraki Gulf.…”
Section: Discussionmentioning
confidence: 99%
“…sydneyanus (Clements et al, 2007 ; Moran et al, 2005 ). We again sampled free‐living animals collected from their natural environment and analysed gut contents from specific regions of the alimentary tract since microbial communities are known to vary along the gut of vertebrates (Donaldson et al, 2016 ), including fish (Jones et al, 2018 ; Parata et al, 2020 ). Sample variation due to season, temperature, location and food source was minimized by collecting all fish on the same day from the same site at Great Barrier Island, Hauraki Gulf.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al 2018 observed highest alpha diversity in the hindgut in the rabbitfish Siganus fuscescens while Gajardo et al 2016 found similar trends in the taxonomically and geographically distinct Atlantic Salmon Salmo salar [ 31 , 75 ]. However, the opposite pattern has also been found, suggesting that alpha diversity trends through the gut may vary by other factors besides gut region [ 23 , 24 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fish gut microbiota is influenced by trophic level ( Liu et al, 2016 ), season ( Neuman et al, 2016 ; Dulski et al, 2020 ), host habitat ( Dehler et al, 2017 ; Dulski et al, 2020 ), and intestinal section ( Parata et al, 2020 ). For example, herbivorous, omnivorous, and carnivorous are the main trophic levels of fish and exhibit differences in gut microbiome composition ( Liu et al, 2016 ; Egerton et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%